Classifying reality - Oderberg, David S. (Hoboken : Wiley, 2013)
Distinguished metaphysicians examine issues central to the high-profile debate between philosophers over how to classify the natural world, and discuss issues in applied ontology such as the classification of diseases. Leading metaphysicians explore fundamental questions related to the classification and structure of the natural worldAn essential commentary on issues at the heart of the contemporary debate between philosophy and scienceInterweaves discussion of overarching themes with detailed material on applied ontology.
Categorial predication / E.J. Lowe -- Nature's joints: a realistic defence of natural properties / D.H. Mellor -- Boundaries in reality / Tuomas E. Tahko -- Contrastive explanations in evolutionary biology / Stephen Boulter -- Animate beings: their nature and identity / Gary S. Rosenkrantz -- Classifying processes: an essay in applied ontology / Barry Smith.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Reality; Classification; Categories (Philosophy); Science -- Philosophy; REFERENCE -- Questions & Answers; Categories (Philosophy); Classification; Reality; Science -- Philosophy; Electronic books